2011
DOI: 10.1039/c1cc11740h
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen self-doped nanosized TiO2 sheets with exposed {001} facets for enhanced visible-light photocatalytic activity

Abstract: Nitrogen self-doped TiO(2) nanosheets with exposed {001} facets (ca. 67%) were synthesized by solvothermal treatment of TiN in a HNO(3)-HF ethanol solution and exhibited much higher visible-light photocatalytic H(2)-production activity than nitrogen doped TiO(2) microcrystallites with exposed {001} facets (ca. 60%) by a factor of 4.1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
186
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(195 citation statements)
references
References 42 publications
7
186
0
2
Order By: Relevance
“…As seen in the XPS spectrum of all three samples presented in Fig. 1, there is a strong peak at 399.3 eV that corresponds to the binding energy of N 1S (Wang et al 2016;Xiang et al 2011). The nitrogen signal, only arising from the amino groups of chitosan, reveals the presence of chitosan in the surface layer of Scheme 2 Preparation of cellulose-chitosan microspheres, crosslinked with epichlorohydrin (CCMS-CL) and non-crosslinked (CCMS), in water-in-oil emulsion.…”
Section: Chemical Characterization By Xps Elemental Analysis and Ft-irmentioning
confidence: 98%
“…As seen in the XPS spectrum of all three samples presented in Fig. 1, there is a strong peak at 399.3 eV that corresponds to the binding energy of N 1S (Wang et al 2016;Xiang et al 2011). The nitrogen signal, only arising from the amino groups of chitosan, reveals the presence of chitosan in the surface layer of Scheme 2 Preparation of cellulose-chitosan microspheres, crosslinked with epichlorohydrin (CCMS-CL) and non-crosslinked (CCMS), in water-in-oil emulsion.…”
Section: Chemical Characterization By Xps Elemental Analysis and Ft-irmentioning
confidence: 98%
“…60% exposed {001} facets, due to the larger surface area of the former compared to the latter material. In this case ethanol acted as a capping agent, hindering the growth of the anatase titania single crystals because of its specific binding with the titania surface via the Ti-O-C bond [52].…”
Section: Doped Anatase Tio 2 With Large Percentage Of {001} Facetsmentioning
confidence: 99%
“…The (001) facet was initially expected to be the most active because of its high surface energy [42,[112][113][114][115], whereas later research suggested that the clean (010) facet with 100% five-coordinate Ti was more active in photooxidation and photoreduction reactions [116]. In particular, Liu et al reported that the photoreactivity of (010) facets of TiO 2 is higher than that of the (101) facets, while the (001) facets showed the lowest photoreactivity [116].…”
Section: Anatase Tiomentioning
confidence: 99%